Komunikasi dalam Perspektif Ulama - S.Z., Nase (Prophetica, 2009)
Communication is a main activity in the practice of tabligh. Therefore, communication skill is required to a mubaligh. Nonetheless, there is another problem when we turn to communication tlypes in Islam world, even in many things, in the perspective of communication science, Islam or Muslim scholar are often not rated as a main source or capable to state a· communication theory. Whereas, Muslim scholars, even since the era of shahabat have been raising the tradition of communication ethics which willing to create some communication way according to the ethics of Islam.